Answers

The Brainliest Answer!
2015-07-22T13:05:46+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let the two parts be x and y.
x+y = 12
⇒ y = (12-x)

You need to minimise the sum of their cubes.
(x)³ = x³
(12-x)³ = (12)³ - x³ + 3×12×x² - 3×x×12² = 1728 - x³ + 36x² - 432x

sum, s = (1728 - x³ + 36x² - 432x) + x³ = 1728 + 36x² - 432x
⇒ s = 36x² - 432x + 1728

 \frac{ds}{dx}=0\\ \\ \Rightarrow \frac{d}{dx}(36 x^{2} -432x+1728)=0 \\ \\ \Rightarrow 36 \times 2x - 432+0 =0\\ \\ \Rightarrow 72x-432=0\\ \\ \Rightarrow 72x=432\\ \\ \Rightarrow x= \frac{432}{72}  \\\\\Rightarrow x=6

For minimum, \frac{d^2s}{dx^2} \ \ \textgreater \  \ 0

\frac{d^2s}{dx^2}= \frac{d^2(36x^2-432x+1728)}{dx^2}= \frac{d}{dx}(72x-432)=72\ \textgreater \ 0\\ \\ (condition\ satisfied)

So x = 6,
y = 12 - x = 12- 6 = 6

So the two parts are (6,6)
1 5 1